Repertoires of contention between the regime and political actors - Zarif, Ereny (AUC Knowledge Fountain, 2019)
While most of the literature in post-revolutionary Egypt focused on the international spread of repertoires of contention, protesting, organizing and mobilizing techniques, this thesis aims at drawing links between political action before and after the 2011 uprising through studying 1) the influence of regime's tactics on revolutionary's techniques and 2) political actors’ reactions to the existing structures. Building a bridge between both aisles, regime and actors, and studying them as part of the same construction is crucial. Protesters did not only get affected by international repertoires of contention or local ones, but they were also influenced by the authoritarian regime's tactics, language and institutions. Furthermore, the state borrowed tactics from protesters. For example, the idea of encouraging honorable citizens to act is inspired by the protesters groups who took to the streets. The state borrowed citizens’ engagement from the contentious groups to use it as part of its toolkit to control the vibrant revolutionary waves. The state also borrowed the use of social media and adopted it as a channel of communication. In this research, I will examine groups that were active during the revolution (such as the Ultras groups) and after the revolution (such as the honorable citizens and bearded police officers) to draw analogies of how these movements recycled repertoires of contention that they borrowed from the state and local and international movements. The broader context is important. Concepts like public order must be taken into consideration. I argue that Mubarak regime’s domination of the public sphere before the revolution shaped actions in the public sphere. For example, the dominant one-party regime that Mubarak was leading and the discourse of democracy-without-politics was reflected during the uprising days, when most of the protesters denied any affiliations to political parties. The surveillance and control over stadiums led to training the football fans on how to respond to police forces quickly and cooperatively, which are the skills that they used during the uprising in 2011. And finally, the prohibition of religious markers from some state institutions, either under the umbrella of secularism or long-standing traditions of the entities, paved the way for manipulating the space of uncodified rules. The lack of clear definitions on behalf of the regime, along with the political opportunity that gave the Islamists power after the revolution facilitated this. The bearded police officers used this gap and built a case to gain the right to wear the religious marker to their daily police jobs. I also argue that the state’s tactics inspired actors as to how they should revolt or make demands. The influence worked both ways, meaning that the state learned from the political groups as well.